Plasmodium vivax and Mansonella ozzardi co-infection in North-Western Argentina - Dantur Juri, Maria Julia (2013)
A case of co-infection with Plasmodium vivax and Mansonella ozzardi was detected in a blood sample from a person who had shown symptoms of malaria and lived in a city that was close to the Argentina/Bolivia border. The case was detected during a random revision of thick and thin smears from patients diagnosed with malaria from various towns and cities located in north-western Argentina between 1983 and 2001. Trophozoites of P. vivax were observed in the thin blood smear along with M. ozzardi microfilaria (larval form), which presented a long, slender, pointed anucleate tail and the absence of the sheath. This last characteristic is shared with Mansonella perstans, Mansonella streptocerca and Onchocerca volvulus. More rigorously controlled studies to detect other co-infection cases in the area as well as the possibility of importation from Bolivia into Argentina are currently ongoing. The relationship between the malaria parasite and microfilaria, the potential effect of malaria treatment on the development of M. ozzardi, and the possible impact of this microfilaria on the immunity of a person against P. vivax are all still unknown. This contribution constitutes a point of focus for future studies involving the interaction between the parasites and the potential risk that humans are exposed to.